Nanopartículas magnéticas de 'FE''CO'@'AU': preparação, caracterização e funcionalização com complexo de 'RU'(II) luminescente - Silva, Maria Aparecida Santiago da [UNESP] (2014)
Nanomaterials with magnetic and luminescent properties conjugated in core@shell type nanostructures, also called magneto-luminescent or magneto-optical, have been prepared and are promising as new bimodal agents for applications in bio-imaging. In synthesized core@ shell nanostructures, FeCo alloy magnetic particles were used as magnetic core, because they presente high values of saturation magnetization (MS) in small dimensions, while the gold was chosen as the material for their shell because of its biocompatibility and its surface chemistry that allow the incorporation of new biomolecules and molecular structures in the hybrid core@shell optical components. Different nominal percentage compositions FeCo particles (Fe60Co40, Fe50Co50, Fe40Co60) were prepared by the modified polyol method, using a reducing atmosphere of H2. XRD and ICP-AES analyzes confirm the formation of FeCo alloy, however the particles are likely rust when in contact with air for prolonged periods. The layer of iron oxide on the surface of the particles was confirmed by Mössbauer spectroscopy. Through these measures, we observed for low Fe content FeCo particles greater resistance to surface oxidation upon exposure to air. The magnetic hysteresis curves from vibrating sample magnetic measurements (VSM) suggest the ferromagnetic behavior for all samples. The higher value of Ms (203 emu/g) was obtained for Fe40Co60 particles and it is close to reported one to massive alloys with the same composition. Concurrently, a slight hysteresis loop displacement along the applied field axis is observed in all samples as a result of polarization exchange phenomenon or exchange- bias, which indicates the formation of an oxide layer on the FeCo alloy particles surface and corroborates the observed XRD and Mössbauer data. FeCo particles were coated by an Au layer by the seed-mediated growth method. Molar ratios of FeCo:Au were set to 5:1, 3:1, 2:1 and 1:1 by varying the Au (III)...